CODESRIA Bulletin Online, No. 6, August 2020 - Ernest Wamba-dia-Wamba Bazunini, 1942–2020: Militant, African Intellectual and Friend - Michael Neocosmos (CODESRIA Bulletin, 2020)
On 15 July, in Kinshasa, Ernest Wamba-dia-Wamba Bazunini left this world. No doubt the usual clichés will abound: a “Great Son of Africa!”, “an Intellectual Giant!”, “a Great PanAfricanist!” and so on as people revert to the tired old slogans they regurgitate every time an important intellectual figure joins the world of the ancestors. Wamba would have giggled at this, as was his want. He was keenly aware that behind such empty slogans were precisely empty politics, and that these slogans substituted for what he saw, and deplored, as the absence of political thought among many intellectuals in contemporary Africa. Wamba (as he was known by all) was a rare phenomenon. He was an organic intellectual in the full sense of the term, and one of the greatest on our continent. He lived his life in complete fidelity to his political principles, and at considerable personal cost. He had endured arrest and detention, been a protagonist in armed struggle, and narrowly escaped assassination attempts on several occasions. His principles were founded on drawing all the consequences from the axiom that it is the people and the people alone who are the makers of the emancipatory currents in world history. I had the singular honour of interviewing him over five consecutive days in May 2019 during which our conversations covered all aspects of his politics, and his philosophical thought. In fact, the two were practically indistinguishable. Wamba was totally at ease discussing the state inancient Egypt, the Mobutu regime, the problems of the nationalist movement in Congo, the intellectual debates at the University of Dar-es-Salaam in the 1970s, African spirituality, Pan-Africanism, the politics of the Cultural Revolution in China, the philosophies of Jean-Paul Sartre, Maurice Merleau-Ponty and Alain Badiou, the neo-colonial character of liberal democracy in Africa, the dominance of statist conceptions of politics among ordinary people in Congo, or the sound of the guitar played by Franco the king of Rumba. Wamba was born on the 16th of April 1942 in central Congo in a KiKongo-speaking area. His was a peasant family, and he was deeply immersed in local traditions from his early youth. He learnt his respect and love for humanity from a young age. The values that he learnt were centrally concerned with treating people with dignity and respect. In BaKongo communities, the importance of resolving non-antagonistic contradictions in a manner that was participatory and democratic was absolutely fundamental to holding the community together. It was out of the experience of attending a number of these collective sessions in the form of a Mbongi or Palaver, that he wrote what is probably his most well-known work Experiences of Democracy in Africa: Reflections on Practices of the Communalist Palaver as a Method of Resolving Contradictions among the People. His study of the Palaver was not anthropological. In this study, and throughout his work, he related popular practices and struggles to a politics of emancipation which he was constantly re-thinking and developing. The central concern of politics for Wamba was not war or violent antagonism, but the production of a collective unity. He insisted on the fact that his politics were always directed to bringing peace to the Congo (as it happens the name Wamba means the one who brings peace). In his view, the failure of the state in post-independence Africa was precisely the failure to develop a shared understanding of an idea of the ‘common good’. There are perhaps two dominant themes running through all his intellectual and political work: The importance for the state in Africa to understand the need to manage the ‘common good’ rather than the interests of (neo-) colonialism, and historically its total inability to do so, a fact that implied its failure to adhere to basic universal democratic norms and; the unavoidable centrality of independent popular organisations in emancipatory politics in order a) to hold those in state power to account and thus to insist on genuine popularly-founded democracy and b) to provide the basis for popular movements to defend those who end up in power and attempt to oppose (neo-) colonialism. In Wamba’s view, without popular democratic organisation, PanAfricanism was impossible and Africa will be doomed to continue as a neo-colonial amalgamation of countries ruled by predatory and repressive elites with disastrous consequences for its people. Of course this never meant the abandonment of an idea of class struggle, but rather an insistence on the idea that to effectively engage in political struggles, the unity of the oppressed is an absolute necessity. For Wamba the primary failure of most African intellectuals was a virulent and obvious state fetishism with a consequent inability to theorise politics as being conditional upon emancipatory subjectivities to be founded on the politics of the organised masses, much as was the case with Cabral’s famous notion of ‘Returning to the Source’. Without a popular mass movement there could be no emancipatory politics. The problem of the state in Africa was not so much the absence of institutions, but rather the fact that existing institutions were modelled on the West so that the state – even after independence – remained an external imposition disconnected from the people it was meant to govern. In his well-known expression, the postcolonial state was simply ‘grafted’ onto the pre-existing colonial one, thereby making it impossible to transform Africa along a popularnationalist conception of genuine emancipation. Wamba argued that Africa in general, and Congo in particular, remained the prisoner of a predatory capitalism which systematically engaged in the mass torture of a continent. The result was that, following the colonial ‘civilising mission’, Africa experienced a Western ‘developmental mission’ soon followed by a ‘democratising mission’ in which a travesty of development and democracy were deployed and more frequently imposed. African leaders were, in the main, unwilling to work to support the realisation of the needs of the continent’s people because they allowed their interests to coincide with those of the West. Much like those Chiefs and Kings who had sold their people into slavery, post-colonial African leaders continued to sell their people to Western interests while blaming the latter for the people’s poverty. Wamba stressed that Africans should undertake a study of their own past, including of their popular struggles (and similar ones like the Chinese), in order to elucidate theoretical signs and alternative political conceptions. This required both self-criticism and a thorough spiritual cleansing. Such study could learn much, for example, from the idea of Ma’at in ancient Egypt, which insisted on the maintenance of social balance and an ethical life that venerated justice and truth. The point here being that, even in the conditions of the existence of the Pharaonic state, in other words of extreme power differentials, the interests of minorities excluded from power would be taken care of to a certain degree. In this way, at least some sort of social balance could be maintained and chaos, the main fear of the ancient Egyptians, could be avoided. Of course, this did not always happen in practice. Wamba also invested considerable intellectual energies to an elucidation and examination of the historical predictions and prescriptions of anti-colonial millenarian movements. One of these was the movement in the Congo of the 1920s led by Simon Kimbangu, who predicted the subservience and corruption of post-independence leaders to Western dominance and who insisted on the need to fight the destruction of African languages. For Wamba these movements sometimes expressed political prescriptions that were politically more important than those of many Western-trained academics. He argued that one had to learn from these histories, and, in general, the emancipatory prescriptions emerging from popular ruptures with the order of domination. The philosophical result of these reflections was Wamba’s insistence on knowledge acquisition as a collective as opposed to an individual activity, and on dialectical thought, namely the recognition of contradictions and divisions along with their trajectories, as being at the centre of emancipatory political thinking. These philosophical views dovetailed completely with Wamba’s personal lifestyle and political commitments. At the personal level Wamba was a very spiritual person and would not see his departure from the living as in any way an end point. Rather, the idea that a person’s soul (or whatever one wishes to call it) could be resurrected in someone else was an African belief to which he held strongly. He was fully immersed in ancestral reverence and communication. The coercive separation of Africans from their spirituality was, for him, one of the more nefarious aspects of colonial domination. Wamba’s political involvement began at the age of fourteen when he was elected president of the teachers’ union when he was teaching French to nurses at a medical school. He was also the secretary and then president of the school debating club. His political practice took off from there. He was offered a scholarship to the US where he became part of what was called the Black Action Movement (BAM) in Western Michigan University. He met Stokely Carmichael and received the Robert Friedman Philosophy Prize for his Master’s dissertation. After returning home Wamba entered government as the personal assistant and eventually principal secretary to the Minister of Social Development and Housing. He also had the opportunity to go to France where he met and became involved politically with other philosophers like Alain Badiou and Sylvain Lazarus. Back in the United States he was again involved in student politics teaching a course on The Political Economy of the Third World at Brandeis, Harvard and Boston College. He was part of creating the Student and Workers for African Liberation (SWAL) committee with which he worked politically from 1973 to 1978. He then left for Dar-es-Salaam where he took up a position in the History Department where he ran the History Seminars which became a major centre for intellectual debates. This is where I first meet him in 1982. By then Walter Rodney had left and Wamba became critical of both positions taken in the so-called Dar-esSalaam Debate arguing that, rather than discussing capitalism or socialism, the primary focus should be on neo-colonialism which had to be thought in itself as a new historical epoch. In December 1982 Wamba was arrested in then Zaire (today’s DRC) while travelling through Kinshasa. He was caught with a paper he was writing that was critical of Mobutu’s idea of “Authenticité” which was the dictator’s idea of African nationalism. For Wamba this was simply a neo-colonial notion. As a result of international pressure in the US, France, Britain and Tanzania, and the personal intervention of Julius Nyerere, he was eventually released in December 1983. He later became a member of the National Sovereign Conference (1991-92), which was a genuine attempt by Congolese themselves to establish a new form of state as Mobutu’s power had waned. Mobutu with the backing of the United States managed to frustrate the Conference’s work. From 1992 to 1995 Wamba was the president of the Council for the Development of Social Science Research in Africa (Codesria), which is headquartered in Dakar, Senegal. After ending his term as president of Codesria, Nyerere sought out Wamba’s advice with regard to the Congo. Laurent Desiré Kabila had been in exile in Tanzania but on invading Congo with the support of Rwanda and Uganda Nyerere feared that massacres may take place in Kinshasa. After achieving power, Kabila started persecuting ethnic minorities with the result that an alliance of opposition parties the Rally for Congolese Democracy (RCD) was formed. This alliance of various disaffected groups, ranging from ex-Mobutists, to ethnic Tutsis and Left democrats and radicals, was in search of a presidential figure acceptable to all. In 1988 Wamba was reluctantly persuaded to take up this position which he deemed inevitably necessary as a contribution to liberating his people from centralised state oppression. Nyerere was a particularly important figure in Wamba’s political life because it was he who persuaded him to lead the RCD rebellion against Kabila. Nyerere was able to provide him with support so that the interventions of Rwanda and Uganda within the coalition were restricted. With the death of Nyerere in 1999, that support evaporated and the RCD broke up between an ethnic faction based in Goma and a democratic faction led by Wamba which moved to Kisangani. Although involved in an armed struggle, Wamba was insistent throughout that attempts be made to encourage the development of a popular democratic movement in that part of eastern Congo in order to combat militarism within both state and opposition. For Wamba military power was always to be subordinated to popular democratic power. His attempts to build a movement in the context of war were largely stillborn. The rest, as they say, is history. Wamba’s participation in this struggle was the subject of often vociferous controversy among African scholars in CODESRIA. Unlike many of his colleagues who insisted on the separation between academic work and politics while being linked to states and NGOs, Wamba was a movement intellectual who held that intellectuals should be practically committed to Africa’s liberation. He was vilified by many of his erstwhile colleagues for being ‘subjective’. By committing himself to a struggle he had, in their eyes, crossed a line. Some even accused him of recruiting child-soldiers. This was a pure fabrication, of course, but what upset him most was that few of his African academic friends ever took the trouble to go and see him to listen to his point of view and engage with him. This was the case even when he was in South Africa and Botswana while the negotiations were taking place. Apart from the Zimbabwean Ibbo Mandaza, who wanted to listen to his side of the story, he was almost universally condemned for “mixing politics with academics”. Of course the liberal notion that academic discourse was apolitical and that state democracy allowed for independent thinking were making a comeback at the time. After peace negotiations at Sun City, the war ended in 2003 and Kabila’s son Joseph assumed power and was recognised by states around the world. As part of the compromise Wamba took a position in the Senate where he was a prominent advocate for the subordination of the neo-colonial state to popular democratic practices. However, the new government swiftly collapsed into complicity with neo-colonialism and a predatory relation to society, In his last years Wamba was engaged in developing political discussion groups (he called them Mbongi a Nsi) in Kinshasa and engaging in Pan-African activities while in Dar-es-Salaam. He sustained warm relations with activists, movements, and radical intellectuals around the continent, including here in South Africa where he was seen as an elder by social movement and trade union activists. Wamba’s intellectual work, although published in scattered places, is being brought together by friends. Although he will be sorely missed by many of us, his spirit and work will live among all oppressed people, particularly among those Africans seeking an emancipatory future free from neocolonial domination. It is noteworthy that in a letter expressing his condolences, Alain Badiou emphasised that he cries “for the friend and the militant, and for the thinker and the human being”. In a statement in honour of Wamba, Abahlali baseMjondolo remarked that “Baba Wamba understood that the oppressed have to organise themselves for their own liberation, and he understood that, as well as being open to the whole world, we also have powerful tools within our own culture and history to draw on in the struggle”. Wamba was committed to emancipatory politics, not to social status, irrespective of who engaged in them. Not many people would be remembered in this way by both a leading philosopher in France and some of the most committed and courageous grassroots militants in South Africa. Wamba loved to laugh. On learning that he was a great fan of Franco’s music, I remember asking him, some years ago, why Franco had demeaned himself by writing songs extolling the virtues of Mobutu Sese Seko as a presidential ‘candidate’. I said that it was understandable that he could not be critical of the dictator but that surely there must be limits! Wamba replied “listen to the guitar, it is ironic!” And he laughed and laughed. I’ve been enjoying this irony ever since.